Circulating Endothelial Microparticles in Diabetes Mellitus - A. F. Tramontano; R. Lyubarova; J. Tsiakos; T. Palaia; J. R. DeLeon; L. Ragolia (Mediators of Inflammation)
Background. Endothelial Microparticles (EMPs) are small vesicles shed from activated or apoptotic endothelial cells and involved in cellular cross-talk. Whether EMP immunophenotypes vary according to stimulus in Diabetes Mellitus (DM) is not known. We studied the cellular adhesion molecule (CAM) profile of circulating EMPs in patients with and without Diabetes Mellitus type 2, who were undergoing elective cardiac catheterization. Methods and Results. EMPs were analyzed by flow cytometry. The absolute median number of EMPs (EMPs/𝜇L) specific for CD31, CD105, and CD106 was significantly increased in the DM population. The ratio of CD62E/CD31 EMP populations reflected an apoptotic process. Conclusion. Circulating CD31+, CD105+, and CD106+ EMPs were significantly elevated in patients with DM. EMPs were the only independent predictors of DM in our study cohort. In addition, the EMP immunophenotype reflected an apoptotic process. Circulating EMPs may provide new options for risk assessment.